Results of tailored lateral sphincterotomy for chronic fissure in-ano - Nikhat, Ahemadi Firdous; Ather, Mohd Zaheeruddin (International Surgery Journal, 2019)
Background: Fissure-in-ano is one of the common and most painful anorectal conditions encountered in surgical practice. Inspite of several conservative treatment options, surgical treatment in the form of lateral anal sphincterotomy remains the gold standard of treatment for chronic anal fissure, however it is associated with the significant rate of incontinence. This study reviews using a tailored lateral sphincterotomy by selecting the height of internal sphincter to be divided with aim of preserving more sphincter and hence reducing the incontinence rates. Methods: The study was carried out in 50 patients who were diagnosed clinically as chronic anal fissure attending Surgery department of ESIC medical college and hospital, Kalburagi over a period of 6 months from January 2019 to August 2019. Tailored left lateral internal sphincterotomy was performed in all patients. The date was recorded and analysed. Early post-operative follow-up was maintained every week for four weeks or till the fissure healed. Complications mainly incontinence rate was assessed. Results: Common age group was third and fourth decade of life. Pain (100%) was the commonest symptom. Majority of the patients (96%) had posterior fissure. Postoperatively about 97% patients had complete pain relief. Only one patient (2%) in the study reported incontinence to flatus during the first follow-up visit and had minor incontinence and other minimal complications were found. Conclusions: Tailored lateral anal internal sphincterotomy is safe and effective surgical procedure for the management for chronic anal fissure with lower rate of incontinence rate compared to gold standard lateral internal sphincterotomy.